Evaluation of the clinical pharmacist’s effect on achieving treatment goals in patients with hypothyroidism: a randomized controlled trial - Yunus Emre Ayhan; Muhammed Yunus Bektay; Dilek Gogas Yavuz; Mesut Sancar (BMC Endocrine Disorders)
Abstract Background and aim Hypothyroidism (HoT) treatment involves lifelong thyroxine replacement therapy and regular monitoring. The objective of this study was to assess the impact of clinical pharmacist (CP) intervention in managing drug-related problems (DRPs) on outcomes among patients with HoT receiving levothyroxine (LT4) therapy. Method A randomized controlled trial involved patients with HoT attending a university hospital’s endocrinology and metabolism outpatient clinic from March 2022 to September 2022. Participants were randomly assigned to control (CG) and intervention groups (IG). CP identified and classified DRPs based on Pharmaceutical Care Network Europe (PCNE) v9.1 criteria. The validated version of the Morisky-Green-Levine (MGL) 4-question scale was used to measure adherence. All patients included in the study were assessed during their first visit and again two months later at their second visit. Results 43 patients were assigned to the CG (n = 25) and IG (n = 18). Diabetes (21.6 vs. 20.5%) and hypertension (16.2% vs. 11.7%) were the most prevalent comorbidities in both the CG and IG, respectively. A total of 118 DRPs belonging to both groups were detected. In the IG group, the total number of DRPs significantly decreased from 66 to 24, and the total potential drug-drug interactions (pDDIs) decreased from 21 to 0 between the first and second visits (p < 0.001). CG and IG patients had no difference in adherence levels at the first and second visits (p > 0.05). A statistically significant increase in adherence to the time of taking the medication was observed between the first and second visits in IG (55.5% vs. 94.4%, p = 0.008). Conclusion This study highlights the frequent occurrence of DRPs and LT4 therapy adherence problems in patients with HoT. The findings suggest that the intervention of CPs, by increasing adherence to LT4 therapy and decreasing DRPs, could significantly contribute to improving patients’ treatment outcomes. Trial registration This study protocol has been retrospectively registered at ClinicalTrials.gov (NCT06408909) at 06/05/2024.